Comparison of the activity of brain-derived neurotrophic factor in patients with schizophrenia before and after electroconvulsive therapy - Zakirov, F.; Yuksek, E.; Incir, S.; Saglam, N. G. Usta; Zakirova, B. Kalayci; Emul, M. (ELSEVIER SCIENCE BV, 2016)
29th Congress of the European-College-of-Neuropsychopharmacology (ECNP), Vienna, AUSTRIA, SEP 17-20, 2016